Writing Under the Influence? Salieri and Schubert’s Early Opinion of Beethoven - Gibbs, Christopher H. (Current Musicology, 2003)
In 1822, Schubert dedicated his Variations on a French Theme for Piano Four-Hands, Op. 10 (D624) to Beethoven. This dedication was his most public and extravagant proclamation of an abiding reverence for the older master that he held until his dying day. Indeed, if Ferdinand Schubert is to be believed, his younger brother’s last wish was to be buried near Beethoven, which is exactly what happened (Deutsch 1946:825). A lifelong devotion is implied in Schubert’s letters and plainly stated in the recollections of family and friends. The impress and challenge of Beethoven’s music on Schubert’s is also apparent from the start of his compositional career, and only intensified, I believe, as he matured and engaged with it ever more directly. Beyond purely compositional matters, Schubert modeled his professional career on Beethoven’s in crucial respects and benefited from his relations with many of the same performers, publishers, patrons, and critics who were involved with the older composer (Solomon 1979a; Gingerich 1996; Gibbs 2000). Contemporaries frequently made comparisons between their compositions; as we shall see, critics usually mentioned Beethoven when reviewing Schubert’s piano and chamber works.